2017
DOI: 10.1109/tuffc.2017.2717792
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Strain Imaging With Coherent Compounding of Diverging Waves

Abstract: Current methods of cardiac strain imaging at high frame rate suffer from motion matching artifacts or poor lateral resolution. Coherent compounding has been shown to improve echocardiographic image quality while maintaining high frame rate but has never been used to image cardiac strain. However, myocardial velocity can have an impact on coherent compounding due to displacements between frames. The objective of this study was to investigate the feasibility and performance of coherent compounding for cardiac st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Also, for 256-element layouts the SNR is expected to drop down by 18dB, while for PA+PB the reduction is expected to be 9dB [45]. In general, limited CR and resolution can be improved by employing advanced imaging techniques such as: image coherent compounding, which, even if it limits the frame rate, has already been shown to be effective for cardiac applications based on the transmission of diverging waves [20], [21], [48]; coherence based beamforming methods in reception, enabling both improved spatial resolution and contrast [49]- [52]; adaptive and minimum variance beamformers for artifacts rejection [53]- [56]; the transmission of coded signals for the suppression of cross-talk artifacts in multiline transmission imaging [57], [58]. Also, we showed that mixed array configurations, compared to single array configurations, have a positive impact on CR; nevertheless, a further improvement could be achieved by optimizing the selection of active elements to be assigned to the transmitting and to the receiving arrays [46], [47], [59].…”
Section: Discussionmentioning
confidence: 99%
“…Also, for 256-element layouts the SNR is expected to drop down by 18dB, while for PA+PB the reduction is expected to be 9dB [45]. In general, limited CR and resolution can be improved by employing advanced imaging techniques such as: image coherent compounding, which, even if it limits the frame rate, has already been shown to be effective for cardiac applications based on the transmission of diverging waves [20], [21], [48]; coherence based beamforming methods in reception, enabling both improved spatial resolution and contrast [49]- [52]; adaptive and minimum variance beamformers for artifacts rejection [53]- [56]; the transmission of coded signals for the suppression of cross-talk artifacts in multiline transmission imaging [57], [58]. Also, we showed that mixed array configurations, compared to single array configurations, have a positive impact on CR; nevertheless, a further improvement could be achieved by optimizing the selection of active elements to be assigned to the transmitting and to the receiving arrays [46], [47], [59].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical feasibility and application of several echocardiographic techniques for measuring mechanical properties such as myocardial stiffness are currently being investigated (Correia et al, 2016;Hollender et al, 2017;Melki et al, 2017;Strachinaru et al, 2017;Pislaru et al, 2014;Vos et al, 2017;Bunting et al, 2017b,a;Villemain et al, 2018). Offline post processing of the radio frequency (RF) data is commonly used for improving the image quality of the reconstructed ultrasound sequences and improve tracking accuracy of optical flow methods (Poree et al, 2016;Joos et al, 2018;Song et al, 2013;Grondin et al, 2017). It should be noted that while a high frame rate can be produced with compounding methods such as motion compensation com-pounding, the reduction of temporal resolution is directly proportional to the number of compounded acquisitions and not the frame rate (Joos et al, 2018;Poree et al, 2016;Cikes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Second, compounding can be accomplished with a full transmit aperture and steering of the diverging wave [26]–[28]. Recently, compounding was shown to improve ME strain estimation performance in transthoracic imaging of the myocardium [29]. However, the best transmit parameters for a compounded diverging wave sequence that will maximize cumulative strain estimation accuracy are yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these challenges, it is critical that the imaging sequence used is optimized to estimate strain as accurately as possible. Previously, we have performed investigations into the effect of subaperture, angular aperture, and virtual source number on strain estimation accuracy in partial transmit compounding [24], [29]. However, no extensive investigation into the best transmit parameters for strain estimation of the myocardium with full transmit aperture compounding has yet been performed, nor has any comparison between the two approaches to compounding yet been accomplished.…”
Section: Introductionmentioning
confidence: 99%